PLURILINGUISME ET COMMUNICATION SPÉCIALISÉE. L’EXEMPLE DES TERMES ÉCONOMIQUES - Angela BIDU-VRĂNCEANU; Alice TOMA; Roxana CIOLĂNEANU; Elena MUSEANU (Diversitate si Identitate Culturala in Europa, 2012)
A consequence of the multi linguistics is the apparent facilitation of the scientific communication in the international community, through the quasi-unconditioned loan of the terms from one language to another. But the loan is not without lexical-semantic variations that can affect considerably the accuracy of the scientific communication. This theory is demonstrated in the present paper, mainly, by introducing the concept lexical-semantic discrepancy. To exemplify we chose the economic domain, where the mentioned phenomenon is very frequent. This paper deals with economic Romanian terms proceeded from French, but characterized by lexical-semantic discrepancies, sometimes difficult to see at first sight (Rom. afacere; business / Fr. affaire ; Rom. marca; brand / Fr. marque ; Rom. promovare; promotie / Fr. promotion ). The linguistic analysis proves that the similarities between the respective terms are associated with lexical-semantic discrepancies that can affect the accuracy in communication. The results of this analysis are useful for avoiding the mentioned negative effect.